The Dynamics of Disease in a Regulated Vertically Differentiated Health System - Luca Lambertini; Alessandro Tampieri (Alma Mater Studiorum - Università di Bologna, Dipartimento di Scienze Economiche (DSE), 2011)
We build up a differential game to investigate the interplay between the quality of health care and the presence of an evolving disease in a duopoly where patients are heterogeneous along the income dimension. We prove unicity, stability and perfection of the open-loop Nash solution. Moreover, we identify the admissible parameter region wherein price regulation achieves the twofold objectives of ensuring cares to all patients and eradicating the disease.
Keywords: C73; H42; I11; I18; L13; 330